Could mid-upper arm circumference be a valid proxy to the body mass index for elderly persons? - Anil Kumar Goswami; Ramadass Sathiyamoorthy; Kalaivani Mani; Shashi Kant; Sanjeev Kumar Gupta (Indian Journal of Community and Family Medicine, 2022)
Introduction: In elderly persons, due to physiological, anatomical, and functional changes, body mass index (BMI) may not be suitable for the assessment of nutritional status. Mid-upper arm circumference (MUAC) can be a proxy indicator to identify underweight and overweight/obesity among elderly persons. This study aimed to estimate the correlation between MUAC and BMI, and the cutoffs for MUAC using receiver operating characteristic (ROC) analysis. Material and Methods: This survey was carried out in a resettlement colony of Delhi. The participants were residents of the area who were aged 60 years or older, and selected by a simple random sampling technique. The arm span, weight, and MUAC of the participants were measured. The correlation between MUAC and BMI for gender and age group was calculated. The ROC curve was also constructed. Results: A total of 946 eligible participants were enrolled. The correlation between MUAC and BMI was 0.67 (P < 0.001) and 0.76 (P < 0.001) among men and women, respectively. The MUAC cutoff for underweight was <25 cm with a sensitivity of 68.8% and specificity of 84.9%. The area under the curve (AUC) was 0.84 (0.80–0.88). The MUAC cutoff for overweight/obesity was ≥27 cm with a sensitivity of 83.9% and specificity of 64.9%, and AUC was 0.78 (0.75–0.82). Conclusion: The MUAC of the participants increased as the BMI of the participants increased. MUAC cutoff was determined using the ROC curve for underweight and overweight/obesity among elderly persons.